Transforming Medical Paradigms in 1950s Taiwan. Issue 4 (1st December 2017) - Liu, Michael Shiyung
Abstract : During the early Cold War period, medical reconstruction accelerated in Taiwan with the valuable support of the American medical profession. A common interpretation of this medical reconstruction focused on either the Japanese colonial legacy or the American heritage from China. Both arguments, however, oversimplify the complications inherent in transforming Japanese colonial medicine to meet American criteria of medical service in early Cold War Taiwan. This article explores the confrontation and conflict that made controversial the transition from Japanese colonial medicine to American standard medicine. This review of the history of the changing medical care system in Taiwan identifies a gap between the end of formal colonialism and an invisible colonialism. A new form of colonial medicine in Taiwan unveiled the current global configuration of power and culture during the Cold War in East Asia that was both similar to and different from the historical or imperial-colonial paradigm. Finally, the article touches on some thoughts on new forms of colonial medicine during the Cold War in East Asia.